Fake news during Covid19 in Malaysia: How Ministry of Health encounter fake news contagion in Facebook context - Zaifuddin, Nur Syaheera; Adzharuddin, Nor Azura; Osman, Mohd Nizam; Mohd Zawawi, Julia Wirza (Human Resource Management Academic Research Society, 2023)
The COVID-19 epidemic has become a serious public health concern on a global scale. Malaysians spend an average of eight hours and five minutes each day surfing the internet, as opposed to watching television. In the middle of this, there has been a concealed information pandemic that distinguishes COVID-19 as a digital infodemic with an abundance of false information, rumours, and conspiracy theories. The convenience and accessibility of information sharing on social media has resulted in more misleading information being circulated faster, leading to the propagation of fake news that can damage reputations and lead to social media misjudgements. Stress, anxiety and confusion have been caused by the COVID-19's thorough and repeated content, geographical data and information sources. Because of the anti-vaccine community refuses to acknowledge the facts, the number of Malaysians who are expected to have vaccinations is declining. Their interference merely keeps the government from accomplishing the herd community goal. Due to this, the Malaysian Ministry of Health has faced difficulties in dealing with the spread of misleading news on Facebook since March 2020, despite political tensions and a change of the government. The purpose of this study is to describe many kinds of false information that was spread during COVID-19 and to access how effectively the ministry has dealt with it. By using qualitative method, thematic analysis applied to the social media platform which is Facebook which were identified based on the pages hits on posted headings, pictures, figures and news. The results indicate that there was widespread dissemination of false information on COVID-19, vaccinations, extremist viewpoints, and uncertainty about health measures in Malaysia.